Anaerobic co-digestion of thermal pre-treated sugarcane bagasse using poultry waste. Issue 5 (October 2019) - Vats, Neelam; Khan, Abid Ali; Ahmad, Kafeel
Graphical abstract: Highlights: Co-digestion of sugarcane bagasse with poultry waste for biogas generation. Thermal pre-treatment was carried to check the effect on the anaerobic digestion. Maximum biogas production was obtained at 35:65 (SB:PW) ratio. Abstract: This study investigates the thermal pre-treated (TP) sugarcane bagasse (SB) using poultry waste (PW) for anaerobic digestion (AD) at different (SB: PW) mixture ratios. Six different combinations were made for each set of study i.e. (A and B). Experimental set A consists of batch reactors with untreated SB and PW with 100: 0 (WP0), 85: 15 (WP1), 65:35 (WP2), 50: 50 (WP3), 35: 65 (WP4) and 15: 85 (WP5)ratio. Set B has mixture of thermal pre-treated sugarcane bagasse and PW with mixture ratio of 100: 0 (T0), 85: 15 (T1), 65: 35 (T2), 50: 50 (T3), 35: 65 (T4) and 15: 85 (T5).The retention time of the batch tests were 30 d. Results obtained for biogas generation were modelled using First Order, Gompertz and Logistic Model. Maximum biogas generation of 8916 mL was observed at the ratio of [SB: PW (35:65)] with pre-treated SB using PW.